Analisis Tingkat Pendidikan dan Kemampuan Tenaga Kerja Perempuan terhadap terjadinya Diskriminasi Upah pada Sektor Industri Sedang di Kota Palembang - Luis Marnisah (An Nisa'a, 2017)
The aim of the research was to analyze the impact education and skill of labor market discrimination on the income of medium-sized industry sectors in Palembang. The research was conducted in the city of Palembang with male and female labor force aged 15-64 who worked inmedium-sized industries.Proportional stratified random sampling was employed in selecting 380 labor forces as the sample.The method for collecting the data was survey which is an investigation of gathering factual information from the phenomena, characteristics, behaviors, or opinions of a group of people. This research investigated labor market discrimination in medium-sized industry sectors in Palembang.The research was conducted at sixteen sub-districts in the city of Palembang using questionnaire and observation. Medium-sized industries in Palembangwere purposively selected as the research site of this study. Research variablesincluded factors causing discrimination such as education, working skillsand working experience. The variables that were affected by discrimination include wage and employment. The results revealed that working experience and labor skills have a siginificant influence on labor discrimination in medium-sized industry sector. Meanwhile, education did not significantly influence labor discrimination.It can be concluded that medium-size industries did not require a formal higher education degree. It required competence and skills including technical skills to increase productivity in industry. The variables of education and skills altogether affected labor discrimination significantly as high as 65,1 percent.Discriminations occurred in wage and employment.This could strengthen the relationship among education and working skills. As a result, if labor wage increased, discrimination was likely to increase too. If employment increased, discrimination would also increase.Discrimination had a significant influence on income. This can be seen from the fact that the higher discrimination index, the lower income of the labor force would be.